A Bibliometric Analysis of Comorbidity of COPD and Lung Cancer: Research Status and Future Directions - Fang H; Dong T; Li S; Zhang Y; Han Z; Liu M; Dong W; Hong Z; Fu M; Zhang H (International Journal of COPD, 2023)
Hanyu Fang,1,2 Tairan Dong,1 Shanlin Li,1 Yihan Zhang,1 Zhuojun Han,1 Mingfei Liu,1,2 Wenjun Dong,1,2 Zheng Hong,1,2 Min Fu,3 Hongchun Zhang1,2 1Graduate School, Beijing University of Chinese Medicine, Beijing, People’s Republic of China, 100029; 2Department of Traditional Chinese Medicine for Pulmonary Diseases, Center of Respiratory Medicine, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China; 3Department of Infectious Diseases, Xiyuan Hospital, China Academy of Chinese Medical Sciences, Beijing, 100029, People’s Republic of ChinaCorrespondence: Hongchun Zhang, Department of Traditional Chinese Medicine for Pulmonary Diseases, Center of Respiratory Medicine, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China, Tel +86 13701226664, Email 13701226664@139.com Min Fu, Department of Infectious Diseases, Xiyuan Hospital, China Academy of Chinese Medical Sciences, Beijing, 100029, People’s Republic of China, Tel +86 13366093706, Email bdfumin@126.comObjective: Although studies on the association between COPD and lung cancer are of great significance, no bibliometric analysis has been conducted in the field of their comorbidity. This bibliometric analysis explores the current situation and frontier trends in the field of COPD and lung cancer comorbidity, and to lay a new direction for subsequent research.Methods: Articles in the field of COPD and cancer comorbidity were retrieved from Web of Science Core Collections (WoSCC) from 2004 to 2023, and analyzed by VOSviewer, CiteSpace, Biblimatrix and WPS Office.Results: In total, 3330 publications were included. The USA was the leading country with the most publications and great influence. The University of Groningen was the most productive institution. Edwin Kepner Silverman was the most influential scholar in this field. PLOS One was found to be the most prolific journal. Mechanisms and risk factors were of vital importance in this research field. Environmental pollution and pulmonary fibrosis may be future research prospects.Conclusion: This bibliometric analysis provided new guidance for the development of the field of COPD and lung cancer comorbidity by visualizing current research hotspots, and predicting possible hot research directions in the future.Keywords: COPD, lung cancer, bibliometric analysis, VOSviewer, CiteSpace